2012
DOI: 10.1051/0004-6361/201118634
|View full text |Cite
|
Sign up to set email alerts
|

Swiftfollow-up observations of unclassified ASCA sources

Abstract: We present Swift follow-up observations of a sample of 35 unclassified faint X-ray sources drawn from the ASCA Galactic centre and Galactic plane surveys. Our short, pointed XRT observations allow detections down to a limiting 0.3-10 keV flux of F X ∼ 10 −13 erg cm −2 s −1 , which translates into a luminosity of L X ∼ 10 33 erg s −1 for an assumed distance of D = 8 kpc. The brightest source in our sample reaches a maximum 0.3-10 keV luminosity of L X ∼ 2 × 10 36 (D/8 kpc) 2 erg s −1 during our Swift observatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 62 publications
2
13
0
Order By: Relevance
“…• 2 in diameter; it is difficult to determine precise spectral parameters of such a faint extended source with ASCA. Swift XRT also observed this source for 8 ks on 2007 March, but did not detect it; the upper limit of the flux is 2 × 10 −13 erg cm −2 s −1 in 0.3-10 keV (Degenaar et al 2012). The authors conclude that AX J1836.3−0647 is a strongly variable or transient source because the upper limit is much lower than the flux reported by ASCA.…”
Section: Counterparts To the X-ray Emissionsmentioning
confidence: 72%
“…• 2 in diameter; it is difficult to determine precise spectral parameters of such a faint extended source with ASCA. Swift XRT also observed this source for 8 ks on 2007 March, but did not detect it; the upper limit of the flux is 2 × 10 −13 erg cm −2 s −1 in 0.3-10 keV (Degenaar et al 2012). The authors conclude that AX J1836.3−0647 is a strongly variable or transient source because the upper limit is much lower than the flux reported by ASCA.…”
Section: Counterparts To the X-ray Emissionsmentioning
confidence: 72%
“…SLX 1737-282 is one of the few known LMXB persistently accreting at luminosities lower than L X ∼0.01L Edd (e.g. in 't Zand et al 2005;Del Santo et al 2007;Chelovekov & Grebenev 2007;Degenaar et al 2012;Armas Padilla et al 2013;Degenaar et al 2017). In order to study the spectral and timing properties in this regime, high-quality observations resulting from long exposures, such as those presented here, are essential.…”
Section: Discussionmentioning
confidence: 99%
“…ChI J153818-5541_1 also falls within Region vi in Figure 8 along with these same magnetars, further indicating a possible magnetar nature. However, during the writing of this paper, recent studies with Swift have indicated that ChI J153818-5541_1 (published under its AGPS name AX J1538.3-5541) may in fact be a low mass X-ray binary (LMXB; Degenaar et al 2012). If this is the case, then X-ray and infrared statistical analysis is not a foolproof diagnostic.…”
Section: Chi J153818-5541_1mentioning
confidence: 93%
“…Several unidentified AGPS sources have been investigated by Degenaar et al (2012) using the X-ray telescope (XRT) on the Swift satellite (Gehrels et al 2004). Degenaar et al (2012) suggest that ChI J150436-5824_1 (which they publish under the AGPS name AX J1504.6-5824) could possibly be associated with a main sequence star that falls within the 90% XRT error circle. However, the ChIcAGO Chandra observation of ChI J150436-5824_1 demonstrates that there is no cataloged counterpart within the < 1 position error circle of this X-ray source, arguing against this tentative identification.…”
Section: Chi J150436-5824_1mentioning
confidence: 99%